Analisis Strategi Pemasaran dan Etika Hukum Bisnis yang Berpengaruh Terhadap Kepercayaan Konsumen pada Perusahaan Air Mineral - Aulia Nur Syifani; Halimah Zahrah; Nisrina Nasywa Putri (INDO PUBLISHING, 2025)
The bottled water industry in Indonesia has experienced rapid growth, triggering fierce competition between companies competing to attract consumers through various marketing strategies, including emotional approaches and social campaigns. Marketing effectiveness is not only measured by promotions, but also by compliance with business ethics and regulations, which are the foundation of consumer trust. Consumer trust is crucial to building long-term loyalty and a positive company image. Violations of ethics in marketing, such as negative campaigns or misleading advertising, can damage brand image and trust. This study aims to analyze the influence of marketing strategies and business legal ethics on consumer trust in the Indonesian mineral water sector. This study adopts a qualitative approach with a focus on case studies that analyze documents as the main unit of analysis to determine marketing strategies and business ethics that impact consumer trust in mineral water companies. The results show that mineral water companies in Indonesia implement planned and innovative marketing strategies to attract consumers' attention amidst increasingly fierce market competition. Mineral water companies strive to comply with the Consumer Protection and Prohibition of Monopolistic Practices Law, as well as ensure transparency of information on product labels and advertisements. Ethical marketing practices are an important factor influencing consumer perception and trust. This study confirms that marketing strategies and business legal ethics play a very important role in building and maintaining consumer trust, especially in the mineral water industry which is highly competitive and sensitive to product quality and safety issues.